THE IMPACT OF KNOWLEDGE MANAGEMENT INFRASTRUCTURE IN ACHIEVING ORGANIZATIONAL EXCELLENCE AN EXPLORATORY STUDY OF THE OPINIONS OF A SAMPLE OF TEACHERS AT THE UNIVERSITY OF TIKRIT (World Economics and Finance Bulletin, 2022)
The research aims to study the role of knowledge management infrastructure (culture, technology, structure, human resources) in promoting organizational excellence (the superiority of appropriate strategy, superiority of leadership, superiority of services, business results), The descriptive and analytical approach was adopted, and the study tried to answer the main question of the study problem (what is the role of knowledge management infrastructure in achieving organizational excellence), the study population included (2207) teaching staff at Tikrit University, as a random sample of (326) teachers was chosen, and the statistical analysis program SMART PLS,3) was used . The study reached a set of results, the most important of which is that there is a correlation and effect relationship between the study variable. As for the most important recommendations, it is necessary to pay more attention to aspects of the infrastructure for the purpose of consolidating organizational excellence
Keywords: : Knowledge management infrastructure; organizational excellence